Local stability analysis and numerical simulation of a COVID-19 SEIR Model with vaccination control - Gelera, Francis Angelo R., Jr (College of Science, University of the Philippines Cebu, 2022)
The current COVID-19 pandemic has caused immeasurable damage in all aspects of life all throughout the world. According to the World Health Organization (WHO), the SARS-CoV-2 virus, including the multiple variants it has now evolved to, are the coro- navirus strains responsible for the infectious disease that has taken more than 5 million lives worldwide. It is therefore important to find solutions that would help mitigate the proliferation of the disease and save lives. In this paper, we follow the approach of An- nas et al. [10] and consider an SEIR model with vaccination control of the COVID-19 pandemic. We identify the disease-free and endemic equilibrium points of the model, determine its basic reproduction number ℜ0 using the next generation matrix method, and analyze the local stability of the equilibrium points thereafter. A numerical simu- lation, which supports the theoretical findings is then carried out to explore situations that would emerge out of the model when certain parameters are varied.